Yellow loosestrife (Lysimachia vulgaris var. davurica) ameliorates liver fibrosis in db/db mice with methionine- and choline-deficient diet-induced nonalcoholic steatohepatitis - Yang-Ju Son; Da Seul Jung; Ji Min Shin; Myungsuk Kim; Gyhye Yoo; Chu Won Nho (BMC, 2021)
Abstract Background Nonalcoholic steatohepatitis (NASH), a liver disease caused by a nonalcoholic fatty liver, is increasing in incidence worldwide. Owing to the complexity of its pathogenic mechanisms, there are no therapeutic agents for this disease yet. The ideal drug for NASH needs to concurrently decrease hepatic lipid accumulation and exert anti-inflammatory, antifibrotic, and antioxidative effects in the liver. Because of their multipurpose therapeutic effects, we considered that medicinal herbs are suitable for treating patients with NASH. Methods We determined the efficacy of the alcoholic extract of Lysimachia vulgaris var. davurica (LV), an edible medicinal herb, for NASH treatment. For inducing NASH, C57BLKS/J lar-Leprdb/Leprdb (db/db) male mice were fed with a methionine-choline deficient (MCD) diet ad libitum. After 3 weeks, the LV extract and a positive control (GFT505) were administered to mice by oral gavage for 3 weeks with a continued MCD diet as needed. Results In mice with diet-induced NASH, the LV extract could relieve the disease symptoms; that is, the extract ameliorated hepatic lipid accumulation and also showed antioxidative and anti-inflammatory effects. The LV extract also activated nuclear factor E2-related factor 2 (Nrf2) expression, leading to the upregulation of antioxidants and detoxification signaling. Moreover, the extract presented remarkable efficacy in alleviating liver fibrosis compared with GFT505. This difference was caused by significant LV extract-mediated reduction in the mRNA expression of fibrotic genes like the alpha-smooth muscle actin and collagen type 3 alpha 1. Reduction of fibrotic genes may thus relate with the downregulation of transforming growth factor beta (TGFβ)/Smad signaling by LV extract administration. Conclusions Lipid accumulation and inflammatory responses in the liver were alleviated by feeding LV extract to NASH-induced mice. Moreover, the LV extract strongly prevented liver fibrosis by blocking TGFβ/Smad signaling. Hence, LV showed sufficient potency for use as a therapeutic agent against NASH.